An Acute Comparison of the Change of Serum Lipids, Glucose, and hs-CRP levels After Consumption of a Beef Burger Versus a Vegetarian Burger in Healthy Adults. (29th May 2020) - Barros, Tania Simone; Schompoopong, Maple; Wu, Shih-Ying; Kosch, Cindy; Bains, Gurinder; Berk, Lee; Zamora, Francis; Ji, Liang
Abstract: Objectives: A strong positive association exists between the consumption of fast food and risk of chronic diseases, such as heart disease and type 2 diabetes. Some individuals seek more healthful food alternatives, which include vegetarian products. The fast food industry is investing in more plant-based products. The objective of this study is to compare the change in blood biomarkers (lipids, glucose and high sensitivity C-reactive protein (hs-CRP) levels) after consumption of a beef burger versus a vegetarian burger. Methods: Thirty-five healthy adults (22 females, 13 males), with mean age 28.5 ± 6.1 and mean Body Mass Index 24.4 kg/m² ± 3.5 completed a double blind, randomized, crossover study. After an eight-hour fast, they were randomly assigned to eat either a beef or vegetarian (Impossible) burger. One week later, the burgers were switched. The biomarkers were measured while fasting, and at 30, 60, and 120 min post-burger consumption. Results: Linear mixed model was used for data fitting to assess the effect of adjusted covariates on selected nutrients. Blood triglyceride levels significantly increased from baseline over time after consumption of each type of burger (p ˂ 0.001). Consumption of the vegetarian burger showed significantly faster increase in triglycerides compared to the beef burger (p ˂ 0.001). At 120 min, there was no significant difference in the levels. Low-density lipoproteins significantly decreased over time following both types of burgers (p ˂ 0.001). There was no significant difference between the two burgers. Glucose levels showed significant changes over time for both groups (p ˂ 0.001). There was a significantly (p ˂ 0.004) greater change (initial increase, then decrease) in glucose levels after the vegetarian compared to the beef burger. Glucose levels peaked at 30 min, returning to baseline at 120 min for both groups. There was no significant difference in total cholesterol (p = 0.62), high-density lipoprotein (p = 0.81), or hs-CRP (p = 0.58) within or between groups. Conclusions: Contrary to popular thought, consumption of beef and vegetarian burgers produces similar changes in acute blood biomarkers. Future research is warranted. Funding Sources: This study was supported by Loma Linda University.